Faktor-Faktor Penentu Kepercayaan Muzakki kepada Baitul Mal Aceh - Mahda Yusra; Muhammad Haris Riyaldi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
The management of zakat should apply transparency, accountability and good amil competence in order to gain public trust in zakat management institutions. This study seeks to answer how the effect of transparency, accountability and amil competence on the trust of muzakki in Baitul Mal Aceh as a government agency that manages zakat in Aceh. Data collection using a questionnaire that was distributed to 100 muzakki selected by simple random sampling method. Multiple linear regression analysis was conducted to examine the effect of transparency, accountability and amil competence on muzakki's trust. The results showed that transparency, accountability and amil competence had a positive and significant effect on the level of muzakki's trust in Baitul Mal Aceh, both simultaneously and partially. Baitul Mal Aceh is expected to improve the quality of transparency, accountability and amil competence to maintain the trust of muzakki in order to realize the optimization of the collection of zakat funds in Aceh.